The Effect of Perioperative Probiotics or Synbiotics on Postoperative Ileus in Patients Undergoing Abdominal Surgery: An Evidence-based Case Report - Fabiani, Helena; Lestari, Wiji (The Indonesian Society for Digestive Endoscopy, 2024)
Aims: To explore the effects of perioperative probiotics or synbiotics supplementation on postoperative in patients undergoing abdominal surgery.Method: A literature search was conducted on four databases, PubMed, Cochrane, ProQuest, and Scopus, by using MeSH Term. The article selection process was undertaken by screening the titles or abstracts, reviewing the full texts, and determining their compliance with the inclusion and exclusion criteria. Two systematic review/meta-analysis of randomized controlled trial were critically appraised for validity, importance, and applicability.Results: Perioperative probiotics or synbiotics supplementation may contribute to gastrointestinal function recovery, including reducing postoperative ileus in gastrointestinal cancer. Supplementation of probiotics or synbiotics reduced overall postoperative complications in patients undergoing colorectal cancer surgery and did not cause any side effects. However, the administration of probiotics or synbiotics was not associated with the incidence of postoperative ileus.Conclusion: Perioperative probiotics or synbiotics supplementation can be considered in promoting postoperative gastrointestinal function in abdominal surgery. However, their effect on reducing the incidence of postoperative ileus is still inconsistent.